Tuberculosis outcomes related to the Mycobacterium tuberculosis genotype - O. A. Pasechnik (Sankt-Peterburg : NIIÈM imeni Pastera, 2019)
Mycobacterium tuberculosis strains of different phylogenetic lineages and genetic families differ in biological properties that determine, to some extent, epidemiological features and clinical manifestation in tuberculosis (TB) patients.The aim of the study was to assess the risk of an adverse outcome of the disease in TB patients caused by various M. tuberculosis genotypes.Materials and methods. A total of 425 patients with respiratory TB were enrolled in this study. They were registered at phthisiatric facilities in the Omsk region from March 2015 to June 2017 period and included: males — 73.1%, mean age 39.9 years, females — 26.9%, mean age 42.0 years. M. tuberculosis culture and drug susceptibility testing and DNA extraction were performed in accordance with standard methods. Strains were assigned to the M. tuberculosis Beijing genotype and its epidemiologically relevant clusters B0/W148 and 94-32 by PCR based detection of specific markers. Non-Beijing strains were subjected to spoligotyping.Results. We found that 66.5% isolates belonged to the Beijing genotype, 12.8% — to LAM, 10.1% — to T, and 4.7% — to the Ural genotype. Multi-drug resistance (MDR) to anti-TB drugs was observed in 195 M. tuberculosis strains (45.9%). Moreover, Beijing genotype was more often isolated from patients with MDR-TB infection (PR = 2.09 (95% CI 1.6–2.74) and TB infection associated with HIV infection (PR = 1.14 (95% CI 1.01–1.31). Lethal outcome was double higher in patients infected with Beijing vs. non-Beijing strains, 28.6% vs. 14.0% (PR = 2.03; 95% CI 1.3–3.17). The risk factors were identified as follows: young age 18–44 years (RR = 1.7; 95% CI 1.18–2.7), co-morbidity with HIV (RR = 5.0; 95% CI 3.39–7.45), multiple (RR = 1.7; 95% CI 1.14–2.55) and extensive drug resistance (RR = 2.57; 95% CI 1.35–4.92), and association with the Beijing genotype (RR = 2.0, 95% CI 1.3–3.17).Conclusion. M. tuberculosis spread in the Omsk region is characterised by significant prevalence of the Beijing genotype, associated with multiple and extensive drug resistance. A significant association of adverse clinical outcomes and various factors, including association with the Beijing genotype, requires development of new approaches in the fight against tuberculosis.